Market power and merger control in South Africa - Friedrich Kreuser; Michael Kilumelume; Rulof P. Burger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
We estimate structural, materials, and labour markups for the South African economy at the three-digit industry level for 2012-19. The fall in structural labour and materials markups found for the numerical majority of industries are generally isolated to smaller industries, with industries accounting for a higher proportion of sales generally experiencing smaller downward shifts. We show that materials-based markups are increasing over this period. Upward markup pressure in structural and labour markups are primarily driven by compositional shifts of surviving firms, while materials markup growth is driven by the average firm in a given sector. We show that merger intensity is positively related to structural markup growth, with a 1% increase in the proportion of cumulative mergers over 2013-18 being related to around a 0.27% increase in structural markup growth over the period from 2012 to 2019. We find that large vertical mergers are positively related to structural and materials markup growth while being negatively related to labour markup growth. Large horizontal mergers generally increase labour and structural markups.
Keywords: G34; L11; L4; 330; market power; markups; merger control